1997
DOI: 10.4319/lo.1997.42.1.0178
|View full text |Cite
|
Sign up to set email alerts
|

Trophic effects of sponge feeding within Lake Baikal's littoral zone. 2. Sponge abundance, diet, feeding efficiency, and carbon flux

Abstract: Endemic freshwater demosponges in the littoral zone of Lake Baikal, Russia, dominate the benthic biomass, covering 44% of the benthos. We measured in situ sponge abundance and grazing and calculated sponge‐mediated fluxes of picoplankton (plankton <2 µm) for two common species, Baikalospongia intermedia and Baikalospongia bacillifera. By means of dual‐beam flow cytometry, we found retention efficiencies ranging from 58 to 99% for four types of picoplankton: heterotrophic bacteria, Synechococcus‐type cyanobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
134
1
6

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(148 citation statements)
references
References 32 publications
7
134
1
6
Order By: Relevance
“…Sponges can take up minute particles like viruses (Hadas et al 2006) and 0.1-mm sized beads from ambient water (Leys and Eerkes-Medrano, 2006). Pile et al (1996Pile et al ( , 1997 showed that the sponges used in their studies did not show selective feeding on any component of the plankton community. They suggested that the composition of the plankton community and the variability in the water column can affect sponge nutrition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sponges can take up minute particles like viruses (Hadas et al 2006) and 0.1-mm sized beads from ambient water (Leys and Eerkes-Medrano, 2006). Pile et al (1996Pile et al ( , 1997 showed that the sponges used in their studies did not show selective feeding on any component of the plankton community. They suggested that the composition of the plankton community and the variability in the water column can affect sponge nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may not be surprising because the cryptic biota is dominated by suspension feeders, particularly by sponges (e.g., Vasseur 1977;Richter and Wunsch 1999;Wunsch et al 2002). Sponges are very efficient filter feeders, especially in feeding on particles smaller than 2 mm, like bacterioplankton (e.g., Reiswig 1974;Pile et al 1996;Kö tter and Pernthaler 2002). Smaller differences between cavity and reef water DOC concentrations in Berau as compared to those in Curaçao could be explained by shorter residence times of water in the cavities of the Berau area.…”
Section: Discussionmentioning
confidence: 99%
“…They efficiently process large volumes of water and thereby play important roles in benthic−pelagic coupling (Pile et al 1997, Bak et al 1998, organic matter cycling (Reiswig 1974, Yahel et al 2003 and nutrient element cycling (Southwell et al 2008, Fiore et al 2013. By modifying the biotic and abiotic properties ABSTRACT: Sponges are a dominant component of Caribbean coral reef suspension-feeding communities.…”
Section: Introductionmentioning
confidence: 99%
“…Vazquez-Dominguez et al (1999) pre-sented some succesful flow cytometric experiments to estimate grazing rates on bacteria with fluorescently labeled tracers, and Kuipers and Witte (1999) demonstrated the use of flow cytometry to obtain significant results in a study of the impact of microzooplankton community grazing on different size classes of algae. Pile et al (1997 ) studied trophic effects of sponge feeding on four types of picoplankton, and Monger et al (1999) examined the influence of cell-surface hydrophobicity. Gin et al (1999) studied seasonal and depth variation in microbial size spectra at the Bermuda Atlantic time series station, using dual-beam flow cytometry to generate concentration and biomass size spectra of bacteria and phytoplankton.…”
Section: Size and Biomassmentioning
confidence: 99%